2014
DOI: 10.1007/s10570-014-0418-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of highly electro-conductive cellulosic paper via surface coating of carbon nanotube/graphene oxide nanocomposites using nanocrystalline cellulose as a binder

Abstract: Electro-conductive cellulosic paper has attracted great attention as a promising alternative material in the emerging field of flexible and portable electronic devices. However, the environmentally friendly fabrication of electro-conductive cellulosic paper still remains challenging. Herein, green multiwalled carbon nanotube (MWCNT)/graphene oxide (GO) nanocomposites towards the sustainable development strategy were developed and subsequently used to impart electro-conductivity to cellulosic paper via surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 51 publications
(46 reference statements)
2
41
0
Order By: Relevance
“…In addition, the crystal size of F-CNC and S-CNC was a little larger than that of the pulp sample, while the crystal size of T-CNC was clearly smaller compared to the pulp sample, F-CNC and S-CNC products ( 3b). Similar results were also reported for the CNC suspensions obtained from sulfuric acid hydrolysis (Tang, He, Mosseler, & Ni, 2014). However although the viscosity of F-CNC suspension decreased when shear rate reduced in the range of 0.1-300 s -1 , it was nearly constant when the shear rate was higher than 300 s -1 (Fig.…”
Section: Morphology and Redispersibility Of Cncsupporting
confidence: 87%
“…In addition, the crystal size of F-CNC and S-CNC was a little larger than that of the pulp sample, while the crystal size of T-CNC was clearly smaller compared to the pulp sample, F-CNC and S-CNC products ( 3b). Similar results were also reported for the CNC suspensions obtained from sulfuric acid hydrolysis (Tang, He, Mosseler, & Ni, 2014). However although the viscosity of F-CNC suspension decreased when shear rate reduced in the range of 0.1-300 s -1 , it was nearly constant when the shear rate was higher than 300 s -1 (Fig.…”
Section: Morphology and Redispersibility Of Cncsupporting
confidence: 87%
“…For the past few years, the preparation of cellulose nanocrystals (CNCs) and their application in composite materials have gained increasing attention because of their inherent properties like outstanding mechanical properties (elastic modulus of 130-150 GPa) (Iwamoto et al 2009), high specific surface area (up to several hundreds of m 2 /g) (Ng et al 2015), high length-to-width ratio (up to several hundreds) (Jonoobi et al 2015) combined with low density (1.6 g/cm 3 ) (Moon et al 2011), low thermal expansion (0.1 ppm K -1 ) (Song et al 2013), biodegradability and renewability. Due to their special intrinsic nanostructure and excellent properties, CNCs have wide application potential in nanomaterials, such as aerogels (Mueller et al 2015;yang et al 2015), biomedical materials (Domingues et al 2014;Dugan et al 2013;Jorfi and Foster 2015;Plackett et al 2014), packaging materials (Fortunati et al 2012;Li et al 2013b;Mihindukulasuriya and Lim 2014), optical (Biyani et al 2013;Schlesinger et al 2015) or electroconductive (Lyubimova et al 2015;Ning et al 2015;Shi et al 2013;Tang et al 2014) materials, and several mechanically reinforced nanocomposites (de Castro et al 2015;Habibi 2014;Jonoobi et al 2015;Ng et al 2015;Sapkota et al 2015;Therien-Aubin et al 2015;Yang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The current level of the conductometric sensing platform increased with increasing the weight ratio of TiO 2 in the cellulose. A study of highly electro‐conductive cellulosic paper was reported by Tang and co‐workers via blending nanopaper with CNT/GO nanocomposites . In the preparation process, GO was employed as a dispersant to improve the dispersion of CNTs in water media, and nanocrystalline cellulose derived from cotton fibers was used as a binder.…”
Section: Approaches To Boost Functionsmentioning
confidence: 99%